Functional and Structural Analysis of Predicted Proteins Obtained from Homo sapiens' Minisatellite 33.15-Tagged Transcript pAKT-45 Variants. (27th May 2020) - Shahbaaz, Mohd; Al-Samghan, Awad Saeed; Malik, Arshi; Afaq, Sarah; Alwabli, Afaf S.; Ahmad, Irfan; Hussien, Mostafa A.; Zubair, Mohammad; Fatima, Farha; Begum, Shamina; Alzahrani, Othman; Tarique, Mohammed
Abstract : The spermatozoa are transcriptionally dormant entities which have been recognized to be an archive of mRNA, coding for a variety of functionally crucial cellular proteins. This significant repository of mRNA is predicted to be associated with early embryogenesis and postfertilization. The mRNA transcripts which are tagged with minisatellites have been involved in the regulation of the gene functions as well as their organization. However, very little information is available regarding the expression of the transcripts tagged with minisatellites in spermatozoa. Therefore, in order to understand the functions and the conformational behavior of the proteins expressed from these minisatellite-tagged transcripts, we have performed a detailed in silico analysis using the sequences of the transcripts. The protein predicted from KF274549 showed the functionalities similar to uncharacterized C4orf26 proteins, while that obtained from KF274557 predicted to be a metallophosphoesterase. Furthermore, the structural folds in the structure of these predicted proteins were analyzed by using the homology modeling and their conformational behaviors in the explicit water conditions were analyzed by using the techniques of Molecular Dynamics (MD) simulations. This detailed analysis will facilitate the understanding of these proteins in the spermatozoon region and can be used for uncovering other attributes of the metabolic network.